Tingkat Pengetahuan dan Pemahaman Masyarakat terhadap Konsep Perumahan Berbasis Syariah di Provinsi Jambi - Supeno Supeno; Mhd Ansori; Melly Susiandari; Putri Anelia Anmas; Indah Sundari; Afihilia Rizky Saffanah; Puti Indah Rahmaya (Universitas Batanghari Jambi, 2020)
This research aims to find out how the level of knowledge and understanding of the community towards the concept of sharia-based housing, in Jambi Province. This research uses empirical research method using the method of disseminating lift in the form of a list of questions (quisioner0 directly to the people located in Jambi Province, by sampling as many as 4 (emapt) cities / districts namely Jambi City, Muaro Jambi Regency, Merangin Regency, Muara Bungo Regency and Kerinci Regency. With the conduct of this research will be obtained information on the level of understanding of the community and the level of community understanding about the concept of sharia-based housing. From the results of the study can be concluded that the majority of people in Jambi Province have been aware of the home ownership program with sharia system, while the majority of people in Jambi Province do not know the procedure of home ownership using sharia system; and the majority of the public has understood that the purchase of housing using the Sharia system is more beneficial to the community economy, contributes to the economic development of the people, understands that the purchase of housing with sharia system is free from usury, confiscation and fines and understands the losses experienced if transacting with usury.